2003
DOI: 10.1097/00001888-200311000-00021
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity of the American Board of Internal Medicine Monthly Evaluation Form

Abstract: The ABIM-MEF appears to be reliable and valid. Further, factor analysis results support the ABIM's movement to simplify the monthly evaluation form to the new Accreditation Council for Graduate Medical Education core competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…We had previously shown that both the immediately two preceding versions of the medicine resident evaluation forms had poor validity and reliability. 35 Whether assessments based on the new ACGME Internal Medicine Milestones 36 will truly improve the evaluation process remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously shown that both the immediately two preceding versions of the medicine resident evaluation forms had poor validity and reliability. 35 Whether assessments based on the new ACGME Internal Medicine Milestones 36 will truly improve the evaluation process remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we examined the relationship between ITE scores and ABIM scores for internal medicine residents 15 and found a weak correlation between the two, although residents in the bottom quartile of the ITE were at increased risk of failing the ABIM certification. That study had several limitations, most notably a small study population of 71 residents and just 4 residents who failed the ABIM-CE.…”
Section: Methodsmentioning
confidence: 99%
“…These studies, in turn, built upon previous research showing that clinical performance assessments of learners and clinical teaching assessments, which were originally believed to tap multiple dimensions, measured the broader attributes of humanism and clinical skills (McLeod et al 1993;Durning et al 2003;Silber et al 2004). …”
Section: Conceptual Framework and Qualitative Methodsmentioning
confidence: 99%